Level of Student’s Knowledge of Prevention HPV Depending on University Profile - Dubiel, Sylwia; Rząca, Marcin Stanisław; Węgorowski, Paweł (Journal of Education, Health and Sport, 2019)
Admission: HPV is the most common sexually transmitted. They can lead to the formation of benign skin lesions, as well as to the development of malignant tumors. HPV infection affects both men and women, among others, by starting early initiation of sexual intercourse without mechanical protection, multiple pregnancies and births, smoking, oral sex type. Among women, persistent infection with oncogenic type of HPV can lead to dysplasia, and then to the development of cervical cancer. A key factor in preventing the occurrence of HPV infection and subsequent consequences, is the knowledge and application of the principles of prevention.Purpose of research: Assessment the level of students knowledge of Lublin universities about the prevention of HPV infections depending on the profile of the university.Material and Methods: The study included 108 students of Lublin universities with a medical profile - Medical University (UM - 64%) and the humanities - Marie Curie University (UMCS - 36%). Technique was used and architectural survey questionnaire.Results: Larger belief that condom fully protects against HPV erroneously presented UMCS students (11%) than UM (3%). Early sexual initiation as a factor indicating HPV infection significantly more students of a medical profile (87%) than in the humanities (18%). Students UMCS (33%) rarely combine with HPV infection by skin to skin contact, in combination with the UM students (68%), which also provides a pathway of invasion.Conclusions: 1.Knowledge of young adults about the prevention of HPV and the health consequences of this infection is incomplete. 2.Students in profile non-medical universities have very large deficits knowledge.3. It is necessary to promote better knowledge on the prevention of HPV infection among young adults. 4. Promote a sense of responsibility for their own health and others, indicating the need to undergo periodic testing, prevention and treatment of sexually transmitted infections.